2013
DOI: 10.1021/jp4052352
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Properties of Expanded Porphyrins: A DMRG Study

Abstract: We study absorption spectra and two photon absorption coefficient of expanded porphyrins (EPs) by the density matrix renormalization group (DMRG) technique. We employ the Pariser-Parr-Pople (PPP) Hamiltonian which includes long-range electron-electron interactions. We find that, in the 4n+2 EPs, there are two prominent low-lying one-photon excitations, while in 4n EPs, there is only one such excitation. We also find that 4n+2 EPs have large two-photon absorption cross sections compared to 4n EPs. The charge de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Organic materials such as polymethine dyes [ 1 ], chromophores [ 2 ], phthalocyanines [ 3 ], porphyrins [ 4 ], and their related compounds [ 5 ] are target materials to study nonlinear optical (NLO) properties. The conjugated π-electron bonding networks in these molecules are the principal reason for their typical NLO properties [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials such as polymethine dyes [ 1 ], chromophores [ 2 ], phthalocyanines [ 3 ], porphyrins [ 4 ], and their related compounds [ 5 ] are target materials to study nonlinear optical (NLO) properties. The conjugated π-electron bonding networks in these molecules are the principal reason for their typical NLO properties [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , when two opposite meso‐N atoms are replaced by two pyrrole units, the 18 π‐electron aromatic porphyrin will be changed into a 24 π‐electron anti‐aromatic porphyrinoid ( 14 ) [ 28 ] with the LLDP/IDR as high as (−10.5–−15.5 a.u. )/1307 a.u.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the isomer of 14 / 15, the anti‐aromatic performance of 16 [ 28 ] is really bad. As can be found in Figures 10, if two opposite 2‐methylpyrroles are replaced by two pyridines, the in‐ring LLDP/IDR is immediately reduce from (−10.5–−15.5 a.u.…”
Section: Resultsmentioning
confidence: 99%
“…Ab initio DMRG calculations for neutral systems employing molecular orbitals have bottlenecks since the calculation of two-electron integrals is computationally expensive, and consequently, these studies employ ∼50 active space orbitals [55]. On the other hand, DMRG calculations with localized orbitals have been successfully employed for π-conjugated systems with several hundred pz orbitals within the PPP Hamiltonian [53,56,57,58,59]. The ab initio study of arenes using the DMRG method has also revealed that fully-localized orbitals bring about faster convergence of energies compared to canonical Hartree–Fock orbitals or split-localized orbitals [55], making the localized description the picture of choice.…”
Section: Methodsmentioning
confidence: 99%